H49 The Huntington's disease quality of life battery for carers (HDQOL-CS): evidence from the Huntington's disease burden of illness (HDBOI) study for Europe. (12th September 2022) - Rodriguez-Santana, Idaira; Willock, Rosa; Frank, Samuel; Mestre, Tiago; Hamilton, Jamie L; Stanley, Cath; Vetter, Louise; Hernandez-Jimenez, Elena; Dolmetsch, Ricardo; Ratsch, Sarah; Ali, Talaha M
Abstract : Background: Huntington's Disease (HD) progresses over time, impacting mental health, work productivity and inter-personal relationships of the person with HD (PwHD) and their caregivers. We explore the impact of HD on caregiver's quality of life (QoL) using the Huntington's Disease Quality of Life Battery for Carers (HDQoL-Cs) tool. Methods: The short version of the HDQoL-Cs tool was part of the caregiver questionnaire of the HDBOI study. It has 23 items divided into two components: 'satisfaction with life' and 'feelings about living with HD'. Each item ranges from 0-10 (higher scores reflecting better QoL), and component scores result from the mean score of corresponding items. Caregivers were categorized into three groups according to the disease stage of the PwHD, categorization was based on the opinion of the treating physician. Differences in QoL were explored descriptively using ANOVA tests. Results: The sample has 434 caregivers ( Table 1 ), of which 36% were caregivers of early (ES), 36% of mid (MS) and 27% of advance (AS) stage. Mean score of 'satisfaction with life' decreased for more advanced stages: 6.00, 5.74 and 5.38 for ES, MS and AS respectively [p< 0.05]. Satisfaction with treatment and social environment were the key items driving the satisfaction score. Similar results observed for 'feelings about living with HD' domain: 5.94, 5.31, and 5.12 [p< 0.05]. Stress and exhaustion were the most reported feelings experienced by caregivers. Conclusion: Our results quantify the substantial humanistic burden associated with caregiving duties and highlight that the healthcare and psychosocial support needs of PwHD and their families remain largely unmet.